Associations of bone mineral density with sex hormone-binding globulin (SHBG) and testosterone in middle-aged Saudi men: a cross-sectional study - Yakout, Sobhy M.; Khattak, Malak Nawaz Khan; Al-Daghri, Nasser M.; Al-Masri, Abeer A.; Elsaid, Mohamed A. (Frontiers in Endocrinology, 2023)
The present cross-sectional study examined the association between circulating levels of sex hormone-binding globulin (SHBG) and testosterone with bone mineral density (BMD) in middle-aged Arab men. Clinical data of 103 middle-aged Saudi men (mean age 60.7±7.2) were extracted from the Osteoporosis Registry of the Chair for Biomarkers of Chronic Diseases, King Saud University in Riyadh, Saudi Arabia. Participants were categorized according to the presence of osteopenia (T-score -1.0 to -2.5) (N=47) and controls (N=56). Data collected included demographics and anthropometrics as well as levels of sex hormone-binding globulin (SHBG), testosterone and follicle-stimulating hormone (FSH) which were measured using commercially available assays. Free androgen index (FAI) was calculated. Those with osteopenia had significantly lower levels of FAI (p<0.05), and higher levels of SHBG (p<0.004) and FSH (p<0.005). In the osteopenia group, SHBG was positively correlated with age (r=0.33, p<0.05), while it was inversely correlated with BMD spine (r = -0.39, p<0.05) and T-score femur (r= -0.35, p<0.05) in the same group. Furthermore, testosterone was inversely correlated with BMI in the osteopenia group (r= -0.33, p<0.05) while FAI was positively correlated with T-score femur (r = 0.36, p<0.05) as well as in all participants (r= 0.24, p<0.05). Among controls, FAI had an inverse correlation with FSH (r= -0.28, p<0.05) and over-all (r= -0.22, p<0.05). In summary, the associations elicited suggest that circulating levels of SHBG and FAI may be against age-related bone loss in middle-aged men.